A qualitative exploration of women's experiences discovering pregnancies in the emergency department() - Roberts, Sarah C.M. (Contracept X, 2020)
OBJECTIVES: The few studies examining pregnancy testing in emergency departments (EDs) address pregnancy-related physical risks. Here, we examine experiences of people who discover pregnancies in EDs. METHODS: Between 2015 and 2017, as part of a larger study, we conducted interviews with 29 women in Southern Louisiana (n = 13) and Baltimore, MD (n = 16), who reported discussing their pregnancy during an ED visit. We analyzed these interviews for content and themes. RESULTS: Respondents reported diagnosis of pregnancy as a routine and straightforward component of care received in EDs. They reported receiving diagnostic studies and therapeutic interventions to rule out and treat complications of pregnancy and care for what brought them to the ED to begin with, such as treatments for nausea and vomiting; education about physical symptoms and nutrition-related needs during pregnancy; and referrals to prenatal care. However, we find evidence of unmet needs related to patient-centered communication, such as providing emotional care to women discovering pregnancies in EDs and lack of support for transitions to abortion care. CONCLUSIONS: While diagnosis of pregnancy in the ED may be routine for ED clinicians, it is not necessarily routine or straightforward for people receiving the diagnosis. ED clinicians should not assume that all people who discover their pregnancies in the ED want to continue their pregnancy. People who discover pregnancies in EDs may benefit from patient-centered communication and support for the range of transitions to care people might need in addition to the routinely provided diagnostic and therapeutic interventions. IMPLICATIONS: ED clinicians may need additional training and support to ensure that they can meet the range of needs of people who discover their pregnancies in the ED.